Histórias de velhos: fazendo as pazes com a vida - Araújo, Vivian Andrade (2015)
In the last three decades of the twentieth century, aging and old age began to draw attention as important issues for society. The theme has received the most varied considerations. In this study we focus on the possibilities of a very satisfactory aging experience of life. To perform this research we collected life stories of people over 80 years old to establish relations between the stories of each the subjects and how they live their old age. We identified significant moments, how they built their stories and the recurrence among the participants. These are revealed, for instance, by the appreciation of stories occurring within the family circus, by education as a possibility of growth and emancipation and even so by the difficulties faced during their lives. One of the goals was to understand, from the speech of the subjects, the way old age emerges in their stories and also identify the perceptions of old age and aging with the people over 80 years of age ( older elderly according to IBGE classification). Regarding this a surprise happened: only a few aspects of aging and old age appeared, the most frequent thing was life as it is presented, independent of the period of life where the subject is in. It was observed that the subjects live what life presents for them or what they intended to. Herein lies the meaning of life for them, to live life without pre-determinations or prejudices; life rises and it has to be lived, the good parts and also the bad